2021
DOI: 10.1016/j.omtn.2021.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Non-targeting control for MISSION shRNA library silences SNRPD3 leading to cell death or permanent growth arrest

Abstract: In parallel with the expansion of RNA interference (RNAi) techniques, accumulating evidence indicates that RNAi analyses might be seriously biased due to the off-target effects of gene-specific short hairpin RNAs (shRNAs). Our findings indicated that off-target effects of non-targeting shRNA comprise another source of misinterpreted shRNA-based data. We found that SHC016, which is one of two non-targeting shRNA controls for the MISSION (commercialized TRC) library, exerts deleterious effects that lead to elimi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…They demonstrated how erroneous RNAi data led to selection of incorrect targets for cancer therapy and even to initiation of clinical trials, which were bound to fail. In our previous work we reported that also control shRNA, which by definition should not influence expression of any gene, might elicit powerful off-target effects that invalidate the reliable interpretation of RNAi data ( Czarnek et al, 2021 ). Thus, in the case of shRNAs application, off-target effects seem to be a common phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrated how erroneous RNAi data led to selection of incorrect targets for cancer therapy and even to initiation of clinical trials, which were bound to fail. In our previous work we reported that also control shRNA, which by definition should not influence expression of any gene, might elicit powerful off-target effects that invalidate the reliable interpretation of RNAi data ( Czarnek et al, 2021 ). Thus, in the case of shRNAs application, off-target effects seem to be a common phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Oligonucleotides encoding the shRNA sequences ( ) were annealed in 1×Taq buffer and ligated into linearized plasmids. Lentiviral vectors were produced as described previously ( Czarnek et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The pSBbi‐Pur‐dCas9‐KRAB‐meCP2‐hU6‐sgRNA‐SapI plasmid, used for Reg‐2 knockdown was a gift from Maria Czarnek 45 . sgRNA sequence targeting Zc3h12b was designed using the CHOPCHOP tool 46 .…”
Section: Methodsmentioning
confidence: 99%
“…In all settings and if not stated otherwise, RMS cells transduced with either the empty pBABE or the empty pGIPZ vectors served as respective controls [CTR; please note that it was decided to use an empty vector for the WNT5A shRNA validation experiments, because an empty vector was also used for the WNT5A overexpression experiments. In addition, empty vectors are frequently used in knockdown experiments ( 27 , 28 )]. pBABE and GIPZ plasmids both contain a puromycin resistance cassette.…”
Section: Methodsmentioning
confidence: 99%